Belonging and whakapapa : the closed stranger adoption of Māori children into Pākehā families : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work, School of Health and Social Sciences, Massey University, Aotearoa New Zealand - Haenga Collins, Maria (Massey University, 2011)
Between 1955 and 1985, approximately forty-five thousand closed stranger adoptions took place in Aotearoa New Zealand, with adoption directly affecting twenty-five per cent of the total population. A significant proportion of closed stranger adoptions involved children who could claim Māori ancestry through at least one of their birth parents. The majority of these Māori children were placed within Pākehā families. This research explored the narratives of six self-identified Māori adults who were adopted into Pākehā families by way of closed stranger adoption. The study utilised a Māori-centred research approach, and a thematic narrative analysis of the participants’ accounts was undertaken. The study found that adoption is not a one off event, but is an on-going life experience. The multiple and complex ways the participants narrated their cross-cultural adoption experience reflected the diverse and contradictory narratives Māori adopted into Pākehā families navigate. The narratives clustered around the idea of ‘walking between worlds’, with two major themes of ‘belonging’ and ‘whakapapa’ emerging from the analysis process. Participants told stories on a continuum between ‘belonging’ and ‘not belonging’ within their birth and adoptive families, and in Māori and non-Māori worlds. Specific to Māori in Aotearoa New Zealand is ‘belonging’ through whakapapa. Whakapapa is essential to a Māori identity and to whānau inclusion. This study found that without knowledge of whakapapa, Māori become socially and culturally invisible within te ao Māori. In the telling of these narratives, participants have sought to repair the rupture in their lives when the dominant familial narrative of growing up in a birth family with a shared cultural heritage was not possible. For Māori adopted into Pākehā families, their identities as Māori and as adopted people are inseparable.
Keywords: Interracial adoption; Adoptee identity; Maori adoptees; Maori identity; Cross-cultural adoption